2003
DOI: 10.1002/ejic.200300150
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of Alkylzirconium Complexes Incorporating Asymmetrically Substituted ansa Ligands − X‐ray Crystal Structure of [Zr{Me2Si(η5‐C5Me4)(η5‐C5H3Me)}(CH2Ph)Cl]

Abstract: The monoalkyl complexes [Zr{Me 2 Si(η 5 -C 5 Me 4 )(η 5 -C 5 H 3 R)}(RЈ)Cl] [R = Me, RЈ = CH 2 Ph (1); R = Me, RЈ = CH 2 SiMe 3 (2); R = iPr, RЈ = CH 2 Ph (3); R = iPr, RЈ = CH 2 SiMe 3 (4); R = SiMe 3 , RЈ = CH 2 Ph (5); R = SiMe 3 , RЈ = CH 2 SiMe 3 (6)] have been synthesized by the reaction of the corresponding ansa-metallocene dichloride complex and 1 equiv of the alkyl Grignard reagent. Dialkyl complexes with large alkyl groups only formed for the zirconocene complex containing the ansa ligand Me 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Compounds 12 – 15 were characterized by spectroscopic methods, and complexes 12 and 13 were amenable to X‐ray diffraction studies. We have previously demonstrated that alkylation of silicon‐bridged ansa ‐zirconocenes is controlled by steric interactions between the alkyl ligand and the substituent on the cyclopentadienyl or similar group 31. The 1 H NMR spectra of these complexes show two unique signals at high field (between δ = –0.2 and –1.7 ppm) corresponding to the metal‐bonded methyl groups, thereby confirming dialkylation of the ansa ‐metallocene complexes.…”
Section: Resultsmentioning
confidence: 77%
“…Compounds 12 – 15 were characterized by spectroscopic methods, and complexes 12 and 13 were amenable to X‐ray diffraction studies. We have previously demonstrated that alkylation of silicon‐bridged ansa ‐zirconocenes is controlled by steric interactions between the alkyl ligand and the substituent on the cyclopentadienyl or similar group 31. The 1 H NMR spectra of these complexes show two unique signals at high field (between δ = –0.2 and –1.7 ppm) corresponding to the metal‐bonded methyl groups, thereby confirming dialkylation of the ansa ‐metallocene complexes.…”
Section: Resultsmentioning
confidence: 77%
“…Similarly, MgCl(CH 2 SiMe 3 ) has been extensively used [27,28] to produce dialkyl derivatives of many metallocenes with free cyclopentadienyl ligands, whereas related ansa-metallocenes usually yield the corresponding monoalkyl compounds. [29] Consistently the dialkyl complex [Zr{(η 5 The enantiotopic face of the MBI ligand makes these dialkyl compounds, 2Ϫ4, asymmetric molecules with two nonequivalent alkyl groups. The 1 H NMR spectrum of 2 shows two singlets for the Zr-methyl groups, one shifted significantly highfield (δ ϭ Ϫ1.29) compared with the typical value (δ ϭ 0.09 ppm) observed for the other, which was in the range found for related methyl zirconocenes.…”
Section: Methodsmentioning
confidence: 96%